Experimental Study on the Measurement of Water Bottom Vibration Induced by Underwater Drilling Blasting - Gu Wenbin; Chen Jianghai; Wang Zhenxiong; Wang Zhihua; Liu Jianqing; Lu Ming (Shock and Vibration)
Due to the lack of proper instrumentations and the difficulties in underwater measurements, the studies about water bottom vibration induced by underwater drilling blasting are seldom reported. In order to investigate the propagation and attenuation laws of blasting induced water bottom vibration, a water bottom vibration monitor was developed with consideration of the difficulties in underwater measurements. By means of this equipment, the actual water bottom vibration induced by underwater drilling blasting was measured in a field experiment. It shows that the water bottom vibration monitor could collect vibration signals quite effectively in underwater environments. The followed signal analysis shows that the characteristics of water bottom vibration and land ground vibration induced by the same underwater drilling blasting are quite different due to the different geological environments. The amplitude and frequency band of water bottom vibration both exceed those of land ground vibration. Water bottom vibration is mainly in low-frequency band that induced by blasting impact directly acts on rock. Besides the low-frequency component, land vibration contains another higher frequency band component that induced by followed water hammer wave acts on bank slope.